Incisional hernia prevention: risk–benefit from a patient perspective (INVITE) – protocol for a single-centre, mixed-methods, cross-sectional study aiming to determine if using prophylactic mesh in incisional hernia prevention is acceptable to patients - Jared Torkington; Tessa Watts; Laurie Smith; Laura Knight; Julie Cornish; Alun Meggy (BMJ Open)
Introduction Incisional hernia (IH) is a common complication of abdominal surgery affecting between 10% and 20% of patients and is associated with significant morbidity along with cost to the National Health Service. With high recurrence rates following repair, focus must be on prevention of IH rather than cure. There is an increasing evidence that patients at high risk of developing IH may benefit from prophylactic mesh placement during their index operation. With recent controversy surrounding the use of mesh in the UK, however, there is little understanding of whether this intervention would be acceptable to patients.Methods and analysis INVITE is a mixed-methods, cross-sectional study to explore patient perceptions of the use of mesh as prophylaxis to prevent IH. Patients with and without IH who have undergone colorectal surgery between 2017 and 2020 in a single UK health-board will be approached to participate. 120 participants will be asked to complete a questionnaire and a subgroup of 24 participants will be invited to semistructured interviews. The primary outcome is to assess the acceptability of prophylactic mesh to patients. Secondary outcomes include understanding patients’ knowledge of IH, and factors that may influence or alter the acceptability of mesh. Questionnaires have been developed using a 5-point Likert scale to allow quantitative analysis. Qualitative analysis of interviews will be conducted using NVivo software and thematic analysis. Data will be presented using the Journal Article Reporting Standards for mixed-methods research.Ethics and dissemination Ethical approval has been granted by REC Wales (22/PR/0678), and the study is currently in setup. All participants will be required to provide informed consent prior to their participation in the study. We plan to report the results of the study in peer-reviewed scientific and medical journals and via presentations at scientific meetings. Results from this study will aid the design of interventional trials using prophylactic mesh.Trial registration number NCT05384600.